Improving downdraft gasifier stability by robust instrumentation and control systems. (December 2017) - Kamble, Prashant; Khan, Zakir; Capper, Sean; Sharp, James; Watson, Ian
Abstract: In updraft, fluidized bed and downdraft gasifiers, tar concentrations are typically produced around the 10-20%, 1-5%, 0.1% levels respectively. If gasifiers are operated under specific conditions a clean syngas with low tar concentrations will be produced [1]. The principal objective of this research is to develop a set of robust and inexpensive instrumentation systems to measure gasification parameters and inform control systems to improve gasification performance e.g. temperature, liquid flow and biomass weight for real time mass balance calculations. In the present case nine K-type thermocouples were connected to different positions on an in-house downdraft gasifier that allowed temperature and mass balance profiling. The moisture / bio-oil flow was measured by a liquid flow sensor that gave real time flow rates (L/min) and total quantities (mL) [2]. The Arduino platform was used as the core of the instrumentation and control system and integrated with Makerplot software (GUI). These systems offered a high level of control and robustness for low cost with an open source protocol, allowing other developers to benefit and expand the core of this research. The results from preliminary runs are presented which is currently allowing ignition optimization and overall system improvements.